Improvement of the Electrochemical Performance of lifepo4 Cathode by Y-Doping - Gautier-Zamora, J; Gautier-Zamora, J; Herrera-Diaz, F; Herrera-Diaz, F; Fuenzalida-Ortiz, F; Fuenzalida-Ortiz, F; Márquez-Mandiola, P; Márquez-Mandiola, P (Cambridge University Press, 2017)
LiFe1-xYxPO4 doped (d-LFP) with amounts of yttrium (0.01% < x < 5% w/w) show a remarkable effect on the electrochemical behavior. The d-LPF samples were investigated on the Li extraction/insertion performance through charge/discharge and capacity-voltage curves. The best performance was attained with Y content of x = 1%. The materials were synthesized by a hydrothermal method and characterized by x-ray diffraction (XRD) and scanning electron microscopy-energy dispersive x-ray spectroscopy (SEM-EDX). The XRD studies showed that d-LPF had the same monoclinic structure as the undoped material. The achieved electrode performance has been attributed to the addition of Y3+ ion by stabilizing the orthorhomic structure. The electrode resistance decreases through the Y-doping. © 2017 Materials Research Society.